Natural rubber dressing loaded with silver sulfadiazine for the treatment of burn wounds infected with Candida spp. - Tanaka, Jean Lucas [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Burd, Betina Sayeg [UNESP]; Pegorin, Giovana Sant'Ana [UNESP]; da Silva, Thainá Venâncio [UNESP]; Guerra, Nayrim Brizuela; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; de Barros, Natan Roberto [UNESP] (Elsevier, 2021)
Millions of people are burned worldwide every year and 265,000 of the cases are fatal. The development of burn treatment cannot consist only of the administration of a single drug. Due to the infection risk, antibiotics are used in conjunction with gels and damp bandages. In this work, an inexpensive curative based on silver sulfadiazine (SS) and natural rubber latex (NRL) was developed to treat burn wounds. It was produced by the casting method. The infrared spectrum presented no interaction between drug and biopolymer. At the same time, electronic micrographs showed that the SS crystals are inserted on the polymeric dressing surface. Mechanical properties after the drug incorporation were considered suitable for dermal application. About 32.4% of loaded SS was released in 192 h by the dressings that also inhibited the growth of Candida albicans and Candida parapsilosis at 75.0 and 37.5 μg·mL−1, respectively. The curative proved to be biocompatible when applied to fibroblast cells, in addition to enhancing cellular proliferation and, in the hemocompatibility test, no hemolytic effects were observed. The good results in mechanical, antifungal and biological assays, combined with the average bandage cost of $0.10, represent an exciting alternative for treating burn wounds.
Keywords: Antimicrobial; Biomaterial; Biopolymer; Dressing; Natural rubber latex; Silver sulfadiazine